Semi-thin Sectioning, Light and Fluorescence Microscopy of Floral Bud to Study Microspore Development in Arabidopsis - Min-Jung Kim; Jungmook Kim (Bio-Protocol, 2016)
Pollen grains are male gametophytes produced within the pollen sacs of the anthers of the flower. Recent genetic studies have revealed several components involved in microspore development (Borg et al., 2009; Berger and Twell, 2011), and yet many components controlling microspore development remain to be identified. Semi-thin sectioning of anthers and light and fluorescence microscopy of floral bud (Kim et al., 2015) are the initial key experiments to characterize Arabidopsis mutants and transgenic plants for understanding the roles of new genetic components during microspore development. Herein, we describe a protocol for semi-thin sectioning of anthers and light and fluorescence microscopy of floral bud in Arabidopsis.